2018
DOI: 10.1139/gen-2018-0054
|View full text |Cite
|
Sign up to set email alerts
|

DNA barcoding of forensically important flies in the Western Cape, South Africa

Abstract: Forensic entomology aids the determination of post mortem interval based on arthropods associated with a deceased body. This relies on the accurate identification of insects that visit the body, particularly first colonisers such as Calliphoridae (Diptera). Traditional species identification though morphological keys can be challenging as immature or closely related specimens can look similar. Some of these challenges have been overcome through “DNA barcoding”, which involves the sequencing of informative regi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…Since, morphological identification can be challenging and at times unattainable due to resemblances among species, particularly in immature stages and sometimes in adults too (Harvey et al, 2003;Cooke et al, 2018), molecular identification of the fly was also carried out in the present study. PCR amplification of COI of C. megacephala was amplified using specific primers which resulted in amplicon of 700 bp.…”
Section: Resultsmentioning
confidence: 99%
“…Since, morphological identification can be challenging and at times unattainable due to resemblances among species, particularly in immature stages and sometimes in adults too (Harvey et al, 2003;Cooke et al, 2018), molecular identification of the fly was also carried out in the present study. PCR amplification of COI of C. megacephala was amplified using specific primers which resulted in amplicon of 700 bp.…”
Section: Resultsmentioning
confidence: 99%
“…This method commonly uses sequences from genes in the mitochondrial genome, such as the cytochrome c oxidase gene subunit I (COI) and II (COII), and the tRNA leucine gene, as markers for distinguishing sarcophagid fly species [9]. The internal transcribed spacer (ITS2) sequence sandwiched between the 5.8S and 28S rRNA genes has also been reported to be useful for identification of Calliphoridae species [10,11]. Wells & Sperling [12] and Wells et al [13] showed that COI, COII, and tRNA leucine sequences enable unambiguous identification of forensically important Calliphoridae and Sarcophagidae species.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, many studies have proved the effectiveness of COI barcodes for the identi cation of many species of Calliphoridae [13,14]. Meanwhile, in GenBank, there are abundant molecular data about Calliphora, sequences of forensic important Calliphora have been published and uploaded online from different regions of the world, such as South Africa, the Caribbean Region, Southern European, the United States and Korea [15,16,17,18], making it possible to systematically study the sequence of Calliphora around the world. However, the molecular identi cation is a destructive approach for sample materials.…”
Section: Introductionmentioning
confidence: 99%